Spectrum of Neurological Disorders Undergoing Plasmapheresis in a Tertiary Care Hospital - Nawaz, Muhammad; Sher, Khalid; Khan, Huma (Biological and Clinical Sciences Research Journal, 2025)
Plasmapheresis is a therapeutic modality widely used in various immune-mediated neurological disorders. Understanding the clinical characteristics, disease spectrum, and treatment outcomes in patients undergoing plasmapheresis can help optimize its use in neurology. Objective: To analyze the demographic characteristics, clinical profile, comorbid conditions, laboratory parameters, and outcomes of patients with neurological disorders treated with plasmapheresis at a tertiary care hospital. Methods: A cross-sectional study was conducted in Ward 28, Department of Neurology, Jinnah Postgraduate Medical Centre (JPMC), Karachi, from November 15, 2024, to February 15, 2025, after obtaining ethical approval. A total of 145 patients aged 15–70 years, of either gender, presenting with suspected neurological diseases and undergoing plasmapheresis, were enrolled using non-probability consecutive sampling. Clinical presentations, diagnoses, and outcomes were recorded and analyzed. Results: The mean age of patients was 40.1 ± 15.6 years, with an average height of 1.7 ± 0.14 meters and weight of 74.11 ± 14.1 kg. Weakness and pain were the most common presenting symptoms, each reported in 72 patients (49.65%). The most frequently diagnosed condition was Guillain-Barré Syndrome (GBS) in 77 patients (53.10%), followed by Myasthenia Gravis (MG) in 36 (24.83%), Neuromyelitis Optica Spectrum Disorder (NMOSD) in 22 (15.17%), and Myelin Oligodendrocyte Glycoprotein Antibody Disease (MOGAD) in 10 patients (6.90%). Conclusion: The findings highlight Guillain-Barré Syndrome as the most common neurological condition requiring plasmapheresis. Variations in demographic and clinical features emphasize the need for localized data to inform diagnostic accuracy and therapeutic strategies in immune-mediated neurological disorders.